Ruang publik dan media sosial: partisipasi politik mahasiswa indonesia (Faculty of Communications Science, Dr. Soetomo University, 2020)
The public sphere has not been effective and is considered lacking a significant benefit to the development of democracy in Indonesia. The assumption of Habermas (1987) in the theory of communicative action is to consider public sphere that have political influence. Social media as a public sphere through communicative action theory Habermas believes that students are free to communicate with each other. Therefore, there is a need for studies to study which social media is needed to increase student political participation. By using a mixed method, namely discussing quantitative and qualitative to find out the use of social media as a public space through more contemporary political communication. The results show that social media has proven to be effective as a public sphere for students and has become the most important part for the interaction, discussion and political aspirations of students in a country that supports democracy. This can be clearly seen that social media has contributed massively and significantly to the development of universal public sphere, accessible to students without sphere and time limits. The reason is that students can hardly access information and challenge their political aspirations. The more open public sphere for students through social media can increase student political participation through dialogic dialogue and this is a good step for the realization of deliberative democracy in Indonesia. Keywords: Social Media; Public Sphere; Communicative Action